PENGENDALIAN IMPOR KEDELAI DALAM UPAYA MEWUJUDKAN KETAHANAN PANGAN NASIONAL - YP, Ni Made Suyastiri (Universitas Sebelas Maret, 2008)
Food is primary necessity for a country. Soybean that contains many essential protein is one of important food of Indonesia. In fact, as raw material of tahu, tempe, soy sauce, and milk industry, it is very popular and consumed by almost all people in Indonesia. Along with population and industrial development, soybean necessity is raising.Soybean almost two million tons is needed every year and 60% soybean necessity fullfilment is imported from other country. Soybean importation is up to 1,1 million per year. Excessive soybean importation cause negative impact for agriculture development and be able to damage domestic industrial agriculture. Furthermore, import dependency can spend many devisa and in long run will threaten food security. This paper is going to explain about soybean importation control as an effort to reach food security.